A General Synthesis of 7-Phenyl-7,13-dihydro-8H-benzo[6,7]azepino[3,2-c]quinolin-8-ones - Dobrowolski, Jeremy C.; Nguyen, Duyen H.T.; Fraser, Benjamin H.; Bhadbhade, Mohan; Black, David StC.; Kumar, Naresh (Synlett, 2019)
Complex benzazepinoquinolone scaffolds can be accessed from the reaction of 2-aminoacetophenones and oxindole derivatives and feature the seven-membered azepine ring moiety commonly found in a range of drug molecules. The described reaction is generally applicable and allows for rapid access to a diverse range of new structures with further potential to build more elaborate molecules.
Keywords: dihydrobenzo[6,7]azepino[3,2-c]quinolinones; heterocycles; condensation; fused-ring systems; quinolones; umpolung